Dopamine signalling adaptations by prolonged high-fat feeding. (June 2016) - Décarie-Spain, Léa; Hryhorczuk, Cécile; Fulton, Stephanie
Highlights: Chronic high-fat feeding modulates dopamine tone and function. The impact of high-fat diet on dopamine-related endpoints is inconsistent. Classification of results according to degree of weight gain is illuminating. Diet-induced obesity dampens dopamine availability and release. Impaired dopamine transporter function is apparent independent of weight gain. Abstract : Prolonged high-fat feeding modulates dopamine tone in mesolimbic and nigrostriatal pathways, an outcome that is proposed to influence food-motivated behaviour and reward sensitivity. Study of the impact of chronic high-fat feeding on dopamine signalling and behavioural function in rodents has yielded highly variable results. Here we attempt to shed light on this literature by cataloguing findings according to the degree of body weight gain. A pattern emerges whereby high-fat feeding leading to full-scale obesity is largely reported to inhibit dopamine availability and release. In contrast, impairments in dopamine transporter function are apparent in conditions of little to considerable weight gain. Identification of the mechanisms underlying the neurobehavioral adaptations to high-fat diet would benefit from greater investigation of associated metabolic consequences.